Conference Report: International conference on Malay medical manuscripts 2015 - Mohd Shafri, Mohd Affendi (IIUM Press, 2015)
The first International Conference on Malay Medical Manuscripts (ICOMMM) 2015 was held at the Banquet Hall, Office of the Campus Director (OCD), International Islamic University of Malaysia (IIUM) Kuantan Campus on 8-9th September 2015. It was officiated by the Deputy Rector (Academic and Planning) of IIUM, Prof. Dr. Torla Haji Hassan in the presence of the Deputy Director of IIUM Kuantan Campus, Deans of Kulliyyah of Allied Health Sciences, Kulliyyah of Pharmacy and Kulliyyah of Science, as well as the Director of Integrated Centre for Research Animal Care and Use (ICRACU).